Molecular characterization of a novel splicing mutation underlying mucopolysaccharidosis (MPS) type VI-Indirect proof of principle on its pathogenicity - Coutinho, Maria Francisca (2020)
Here, we present the molecular diagnosis of a patient with a general clinical suspicion of Mucopolysaccharidosis, highlighting the different tools used to perform its molecular characterization. In order to decrease the turnaround time for the final report and contribute to reduce the "diagnostic odyssey", which frequently afflicts affected families, the proband's sample was simultaneously screened for mutations in a number of lysosomal function-related genes with targeted next-generation sequencing (NGS) protocol. After variant calling, the most probable cause for disease was a novel ARSB intronic variant, c.1213+5G>T [IVS6+5G>T], detected in homozygosity. In general, homozygous or compound heterozygous mutations in the ARSB gene, underlie MPS type VI or Maroteaux-Lamy syndrome. Still, even though the novel c.1213+5G>T variant was easy to detect by both NGS and Sanger sequencing, only through indirect studies and functional analyses could we present proof of principle on its pathogenicity. Globally, this case reminds us that whenever a novel variant is detected, its pathogenicity must be carefully assessed before a definitive diagnosis is established, while highlighting alternative approaches that may be used to assess its effect in the absence RNA/cDNA sample(s) from the proband. This is particularly relevant for intronic variants such as the one here reported. Special attention will be given to the use of reporter minigene systems, which may be constructed/designed to dissect the effect of this sort of alterations, providing an insight into their consequences over the normal pre-mRNA splicing process of the affected gene.